2021
DOI: 10.1038/s41598-021-88277-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of a drought-tolerant variety as adaptation strategy for maize production under climate change in the savannas of Nigeria

Abstract: The Decision Support System for Agricultural Technology Transfer (DSSAT) was used to quantify the impact of climate change on maize yield and the potential benefits of the use of drought-tolerant maize variety over non-drought tolerant variety in savanna ecological zones of Nigeria. Projections of maize yields were estimated for three locations representing different agro-climatic zones and soil conditions, in the mid-century (2040–2069) and end-century (2070–2099) under representative concentration pathways s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
(86 reference statements)
1
11
0
Order By: Relevance
“…We emphasize that all hybrids used in the study belong to a similar maturity group (sown and harvested at the same time); therefore, the result of the higher yield potential was a response to a genetic trait. This is in line with previous studies from different parts of the world [74][75][76][77][78], where authors agreed that future research should involve modifying the maize selection criteria to combine tolerances to both drought and wet condition stresses.…”
Section: Discussionsupporting
confidence: 88%
“…We emphasize that all hybrids used in the study belong to a similar maturity group (sown and harvested at the same time); therefore, the result of the higher yield potential was a response to a genetic trait. This is in line with previous studies from different parts of the world [74][75][76][77][78], where authors agreed that future research should involve modifying the maize selection criteria to combine tolerances to both drought and wet condition stresses.…”
Section: Discussionsupporting
confidence: 88%
“…Although increasing N resulted in increased yield when P was applied, the yield response of maize to N application was less under future climate conditions compared to baseline yield (figures S1-3). The general yield reductions may be attributed to the increases in temperatures since the models projected increase or no change in rainfall depending on the location of the study (Tofa et al 2021). Previous study also revealed that an increase in air temperature might affect maize growth and development (Abraha and Savage 2006, Meza et al 2008, Tachie-Obeng et al 2013.…”
Section: Discussionmentioning
confidence: 88%
“…Four contrasting bias corrected GCMs (CESM1-CAM5, CSIRO-MK3.6.0 HadGEM2-ES, and MRI-CGCM3) from Fifth Coupled Model Inter-comparison Project (CMIP5) were used in for the analysis. Detailed about the four GCMs and changes in rainfall and temperatures based on GCM outputs have been reported in Tofa et al (2021). The climate change impact assessment was carried out by comparing the simulated yield of two maize varieties using the baseline climate data against the simulated yield for the midcentury climate data (2040-2069) and end of century (2070-2099) periods under RCP4.5 and RCP8.5 scenarios.…”
Section: Climate Scenarios For Assessing the Impacts Of Climate Chang...mentioning
confidence: 99%
See 2 more Smart Citations